The TNF-α (–238 G/A) polymorphism could protect against development of severe sepsis. Issue 5 (July 2021) - Hugo Montes, A.; Valle-Garay, Eulalia; Martin, Guadalupe; Collazos, Julio; Alvarez, Victoria; Meana, Alvaro; Pérez-Is, Laura; Carton, José A.; Taboada, Francisco; Asensi, Víctor
Primary responses in sepsis-mediated inflammation are regulated by pro-inflammatory cytokines. Variations in the cytokine genes might modify their transcription or expression, plasma cytokines levels and response to sepsis. Activation protein-1 (AP-1) and NF-κB regulate cytokines gene expression in sepsis. A total of 90 severely septic and 91 non-infected patients were prospectively studied. IL-1α ( –889 C/T ), IL-1β ( +3954 C/T ), IL-6 ( –174 G/C ), TNF-α ( –238 G/A ), TNF-α ( –308G/A ), IL-8 ( –251A/T ) and IL-10 ( –1082 G/A ) SNPs, plasma IL-1β, IL-4, IL-6, IL-8, IL-10, IL-13, IFN-γ, TNF-α and monocyte chemoattractant protein 1 (MCP-1) levels, and AP-1 and NF-κB gene expression by neutrophils were assessed. A allele carriers of TNF-α ( –238 G/A ) SNP were less frequent among septic patients. IL-6, IL-8, IL-10, TNF-α and MCP-1 levels were higher, and AP-1 and NF-κB gene expressions lower in septic patients. Sepsis was independently associated with higher fibrinogen, neutrophils counts and IL-8 levels, lower prothrombin, absence of the variant A allele of the TNF-α (–238 G/A) SNP, and haemodynamic failure. Death was independently associated with a higher APACHE II score, higher IL-8 levels, and the diagnosis of sepsis. TNF-a ( –238 G/A ) SNP could protect against sepsis development. Higher IL-8 levels are predictive of sepsis and mortality.